Feeling Energized: A Multilevel Model of Spiritual Leadership, Leader Integrity, Relational Energy, and Job Performance - Yang, Fu (Journal of business ethics, 2019)
Past research suggests that spiritual leadership plays a pivotal role in enhancing employee job performance, yet we have little understanding of how and when spiritual leadership enhances employee job performance. The present study explores how and when spiritual leadership promotes job performance by examining relational energy as a mediator and leader integrity and relational energy differentiation as boundary conditions. We tested the theoretical model with data gathered across three phases over 12 months from 497 employees and their supervisors in 108 groups. Results showed that the positive relationship between spiritual leadership and job performance was mediated by relational energy. Moreover, we found that leader integrity amplified the mediated relationship between spiritual leadership and employee job performance via relational energy. In contrast, relational energy differentiation weakened this mediated relationship.